Hepatitis B and/or C virus reactivation in patients receiving chemotherapy: An observational study - Navin Nayan,; Arumugam Velappan, (Asian Journal of Medical Sciences, 2024)
Background: Viral hepatitis reactivation occurs during various chemotherapy treatments. Patients with high serum titer levels of Hepatitis B virus (HBV) DNA before chemotherapy and those receiving intensive chemotherapy for hematological malignancies are particularly at risk. Aims and Objectives: This study aimed to determine the incidence, predictors, and clinical significance of HBV and hepatitis C virus reactivations during chemotherapy. Materials and Methods: This prospective observational study was conducted at a tertiary care center. Hepatitis B and C virus status was identified before the initiation of cancer treatment. Liver function was monitored in all patients before each cycle of chemotherapy. Patients with deranged liver function were subjected to repeated viral antigen tests and DNA/RNA titer levels. Results: A total of 110 patients were identified as having hepatitis virus reactivation out of 1190 patients. The sites of malignancy were breast, 39.1% (43 patients); colorectal, 11.8% (13 patients); upper gastrointestinal, 10% (11 patients); ovary, 9.1% (10 patients); hematological malignancies, 8.2% (9 patients); lung, 5.6% (6 patients); genitourinary, 4.5% (5 patients); head-and-neck, 4.5% (5 patients); biliary tract, 3.6% (4 patients); brain tumor, 1.8% (2 patients); and others, 1.8% (2 patients). Most of the patients with reactivation received 5-FU/Capecitabine-based chemotherapy 37.3%, (41 patients), taxane plus platinum (10.9%, 12 patients), taxane only (10%, 11 patients), trastuzumab (8.2%, 9 patients), platinum-based (6.4%, 7 patients), tyrosine kinase inhibitors (6.4%, 7 patients), monoclonal antibodies (MABs) (3.6%, 4 patients), anthracyclines (2.7%, 3 patients), immunomodulators (2.7%, 3 patients), and other agents (11.8%, 13 patients). Conclusion: We recommend that Hepatitis B and C virus Screening must me performed before chemotherapy and that non-reactive patients should be vaccinated.